Assessment on the User Interface of a Select Consumer Mobile Application and its Effect to Purchasing Behaviour of Generation Z - Agapay, Arnel B.; Gutierrez, Ernell Bautista; Cajayon, Menrado V.; Cristobal, Charito S. (Future Science / FSH-PH Publications, 2024)
The research assessed the User Interface of a Select Consumer Mobile Application and its effect to the buying behaviour of Generation Z. The Visual Appeal, Navigational Content and Application’s Data Modelling are used as factors for the Mobile App User Interface while Frequency, Quantity and Timing of Purchase are used for Purchase Behaviour. The research is quantitative in nature and utilized 250 respondents selected by way of purposive and random sampling. Results revealed that, in terms of the User’s Interface, respondents expressed a Strong Agreement on the aspect of usability in terms of features and functionalities of the select Consumer Mobile Application. Similarly, a Strong Agreement is also expressed by the respondents towards influence of the user interface in their Purchasing Behaviour. Also, result revealed that the User’s Interface of the Select Mobile Application Strongly Influenced the Purchasing Behaviour of the respondents.